A COMBINATION OF GREY RELATIONAL ANALYSIS AND MINIMIZATION OF REGRET METHOD IN INTERVAL-VALUED INTUITIONISTIC FUZZY SET: CASE STUDY IN SELECTION PROCESS OF SALES ON MANGO-BASED BEVERAGES - MERLIN, M. MARY MEJRULLO; MYSTICA, A. ROSA (International Journal of Mathematical Archive, 2018)
The main scope of this research work is to propose a new formulation by combining the concept of Grey relational analysis and minimization of regret methods to do multiple attribute evaluations and studied for an Interval-valued Intuitionistic fuzzy set. In this research, a real-life problem is given to expose the practicality and effectiveness of the proposed method.